Analisis Pembelajaran Berbasis Masalah dalam Pembelajaran Pendidikan Pancasila Materi Hak dan Kewajiban pada Kelas 5 SD - Vega Kharisma; Octarina Hidayatus S; Endang Suprihatin (Journal Innovation In Education, 2024)
This research aims to determine the application of Problem-Based Learning in teaching Pancasila Education regarding Rights and Obligations to grade 5 students at SDN Bantengan 01, Wungu District, Madiun Regency, including its application and advantages and disadvantages. This research uses a descriptive-qualitative research approach. Data collection was carried out by direct observation, interviews and documentation. In analyzing data, researchers used qualitative data analysis which was carried out interactively and took place continuously. The research results show that planning for implementing Problem-Based Learning in Pancasila Education learning is carried out by setting goals to be achieved, designing learning problem situations that are adapted the learning objectives and materials, and preparing supporting equipment. Class management is carried out by placing students into study groups. The application of Problem Based Learning is carried out by introducing material to students, giving students learning problems, discussing to find solutions to problems, and finding solutions to learning problems. The advantages of implementing Problem Based Learning are that students can think critically, increase understanding of subject matter, there is an increase in learning activities through student-centred learning. Meanwhile, the disadvantage that not all students have the same basic experience regarding the learning problems offered by the teacher.